Effectiveness of cognitive behavior therapy in comparison to CBT- plus play therapy among children with post-traumatic stress disorder in Manado, Indonesia - Sarimin, Dorce Sisfiani; Tololiu, Tinneke A. (International Journal of Research in Medical Sciences, 2017)
Background: Disaster may bring such impacts as PTSD. Concerning flood that befell in Manado City, this study examined the effectiveness of CBT and CBT-plus intervention to overcome PTSD among school-age children that have been affected by flood disaster in this city. Methods: This quasi experiment pre-post-test study was done two a total of sixty children, divided into CBT group and CBT plus group. Play therapy was employed to for CBT plus group to see the difference of the PTSD score in comparison to the CBT only group’s PTSD score. Results: There were decreases in the score of PTSD among the children both in CBT only group and CBT plus group. Play therapy in CBT plus group could give higher reduction in PTDS score in comparison to children who received CBT only intervention. Conclusions: CBT plus intervention is proven effective in reducing PTDS score among children who are affected with PTDS.